1983
DOI: 10.3109/01050398309076249
|View full text |Cite
|
Sign up to set email alerts
|

Sound Levels Recorded Within the Symphony Orchestra and Risk Criteria for Hearing Loss

Abstract: Investigations into noise-induced hearing loss should consist of two parts: a mapping of the sound environment and a charting of hearing loss. This paper is the first part of such an investigation: a mapping of sound levels and sound spectra within the symphony orchestra. It was found that 'heavy' symphonic music exceeds the permitted dose for industrial noise equivalent to 85 dB(A) for a full working week. The permitted noise dose is reached for 'heavy' music after a working time of 10 hours per week in 'expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 2 publications
0
17
0
4
Order By: Relevance
“…The study group comprised musicians playing violin (17), viola (8), cello (7), trombone (4), oboe (4), flute (3), trumpet (3), bassoon (2), double bass (2), clarinet (2), guitar (1), tube (1), harp (1), percussion (1) and horn (1).…”
Section: Subjectsmentioning
confidence: 99%
“…The study group comprised musicians playing violin (17), viola (8), cello (7), trombone (4), oboe (4), flute (3), trumpet (3), bassoon (2), double bass (2), clarinet (2), guitar (1), tube (1), harp (1), percussion (1) and horn (1).…”
Section: Subjectsmentioning
confidence: 99%
“…Their findings indicated that players of particular instruments such as percussion, timpani, trumpets, and horns were at greatest risk of exposure to excessive sustained and peak noise levels (see Table II-V from O'Brien et al, 2008). In addition, other researchers have documented that sound levels recorded during rehearsal and performances sometimes meet or exceed Occupational Safety and Health Administration (OSHA) limits (Axelsson & Lindgren, 1981;Jansson & Karlsson, 1983;Royster, Royster, & Killion, 1991).…”
mentioning
confidence: 99%
“…On the other hand, Figure 3 shows variability of exposure due to changes in repertoire. Several scientists studied musicians' exposure to sound [1,2,3,4,5,6,7,8]. Recently, O'Brien, Wilson and Bradley recorded noise levels within a professional orchestra over 3 years to provide a greater insight into the orchestral noise environment [7].…”
Section: Exposure To Orchestral Noisementioning
confidence: 99%
“…In particular, exposure to excessive sound (so-called orchestral noise) in professional orchestras has been studied. Professional orchestral musicians are often exposed to sounds at levels exceeding the upper ex posure action values from Directive 2003/10/EC [1,2,3,4,5,6,7,8,9]. Although industrial workers are at a higher risk of developing hearing loss, musicians can also develop noise-induced hearing loss (NIHL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation